Dinamīkiyāt Iktisāb Mahārāt al-Taḥadduth bil-Lughah al-ʿArabiyyah: Istikshāf al-Kafā'ah al-Lughawiyyah: Dinamika Perolehan Keterampilan Berbicara dalam Bahasa Arab: Eksplorasi Kemahiran Berbahasa - Azisi Azisi; Nurfaiza Nurfaiza (STAI Nurul Huda Kapongan Situbondo, 2024)
This study explores the impact of Arabic language learning strategies on students' speaking proficiency through Stephen Krashen’s language acquisition hypotheses. Using a qualitative case study, data were collected from non-Arabic-speaking students and lecturers at STAI Nurul Huda and UII Dalwa Pasuruan in Indonesia through interviews and classroom observations. Findings highlight contrasting approaches STAI Nurul Huda emphasizes an immersive language environment (bī’ah lughawiyah) for consistent practice, while UII Dalwa incorporates technology and real-world applications, such as internships and language apps, fostering adaptability and engagement. Challenges include the overemphasis on grammatical accuracy, inhibiting fluency and creativity. Strategies aligned with Krashen’s hypotheses, focusing on meaningful input and reduced anxiety, significantly improved speaking confidence and proficiency. This study emphasizes blending traditional immersion and technology-enhanced methods to develop adaptive, effective language programs. The findings contribute to global Arabic education by advocating for innovative, learner-centered teaching approaches